2020
DOI: 10.1088/1755-1315/418/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth promoting effects of indigenous rhizosphere and endophytic bacteria on soil fertility and black pepper (Piper nigrum) yield at Bangka Belitung

Abstract: Black pepper cultivation in Bangka Belitung is commonly followed a shifting cultivation method. This is due to the low soil fertility. The study aimed to obtain the best combination and concentration of indigenous rhizosphere and endophytic bacteria to improve soil fertility and enhanced growth and yield of black pepper. The study was set up in a complete randomized block design, 9 treatments and 3 replications. The treatments were the combinations of the types and concentrations of the bacterial isolates, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The interaction analysis result showed that at the same 100% P according to the recommendation, yield in the treatment without bacteria was lower than those in the treatments supplied with the mixture B. silvatlantica L-VT09 and N-VT06, with only the L-VT09 strain and with only the N-VT06 strain (Figure 2). This was in accordance with the study by Kartikawati et al (2020), where supplying the mixture of bacterial endophytes Pseudomonas sp., Brevibacillus sp., and Mesorhizobium sp. promotes growth and yield in black pepper.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The interaction analysis result showed that at the same 100% P according to the recommendation, yield in the treatment without bacteria was lower than those in the treatments supplied with the mixture B. silvatlantica L-VT09 and N-VT06, with only the L-VT09 strain and with only the N-VT06 strain (Figure 2). This was in accordance with the study by Kartikawati et al (2020), where supplying the mixture of bacterial endophytes Pseudomonas sp., Brevibacillus sp., and Mesorhizobium sp. promotes growth and yield in black pepper.…”
Section: Discussionsupporting
confidence: 92%
“…Levels of P fertilizer and supplementations of bacteria had not affected values of pHH2O, pHKCl, EC, total N and total P in soil yet (Table 2). According to Kartikawati et al (2020), the bacterial endophytes Pseudomonas sp., Brevibacillus sp., and Mesorhizobium sp. are able to improve the chemical characteristics of soil for pepper.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus pacificus strain EB422 is an endophytic bacterium, and Brevibacillus parabrevis strain GF13 is a rhizosphere bacterium. Both bacteria produce IAA, solubilized P, and fixed N [19]. However, the combination had an insignificant effect on the growth and yield of stevia.…”
Section: N P and K Nutrients Uptakementioning
confidence: 98%